Development of technology and recipe of sweet buns enriched with food additives - M. A. Kazimirova; T. V. Pershakova; A. N. Matvienko; T. A. Shakhray; O. V. Fedoseeva (Новые технологии, 2018)
The article presents data on the effect of the method of application of "Tomato Powder" and "Topinambur Powder" food additives on technological modes of production and quality of sweet bakery products. On the basis of studies technological modes of production of sweet bakery products enriched with "Topinambur Powder" and "Tomato Powder" food additives have been developed. Рroduction recipe of "Topitam" bun enriched with functional ingredients contained in "Topinambur Powder" and "Tomato Powder" food additives has been developed.